2007
DOI: 10.1161/hypertensionaha.107.087759
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5A Inhibition Induces Na + /H + Exchanger Blockade and Protection Against Myocardial Infarction

Abstract: Abstract-Acute phosphodiesterase 5A inhibition by sildenafil or EMD360527/5 promoted profound inhibition of the cardiac Na ϩ /H ϩ exchanger (NHE-1), detected by the almost null intracellular pH recovery from an acute acid load (ammonium prepulse) in isolated papillary muscles from Wistar rats. Inhibition of phosphoglycerate kinase-1 (KT5823) restored normal NHE-1 activity, suggesting a causal link between phosphoglycerate kinase-1 increase and NHE-1 inhibition. We then tested whether the beneficial effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 46 publications
(50 reference statements)
6
40
0
24
Order By: Relevance
“…LV weight was divided by tibial length to determine the LVMI. In 2 rats out of each group ventricular tissue was fixed in buffered 10% formaldehyde and paraffin embedded to stain with picrosirius red for determining collagen volume fraction as previously described [17]. Perivascular collagen was excluded from this measurement.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…LV weight was divided by tibial length to determine the LVMI. In 2 rats out of each group ventricular tissue was fixed in buffered 10% formaldehyde and paraffin embedded to stain with picrosirius red for determining collagen volume fraction as previously described [17]. Perivascular collagen was excluded from this measurement.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Because activation of PI3K/Akt (Snabaitis et al, 2008) or PKG (Pérez et al, 2007) inhibits NHE-1 activity, we examined whether the effect of H 2 S involves these pathways. As shown in Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This is in line with our previous results in which PDE5A inhibition after coronary artery ligation significantly ameliorated postmyocardial remodeling and left ventricular dysfunction in rats. 16 It is important to note that NHE-1 inhibition through SIL seems not to influence cardiac function and growth under basal conditions, probably limiting by this way potential undesired effects. Based on our previous and present findings, as well as those from others, 13,15,37,38 PDE5A inhibition seems to emerge as an important therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study we reported a possible link between both therapeutic strategies: chronic treatment with SIL improved postmyocardial infarction remodeling and function through PKGdependent inhibition of the NHE-1. 16 However, other cellular targets have been also proposed to underlie the cardioprotective effect of SIL. 15,36 In the present study we provide insight into the intracellular pathway involved in the NHE-1-inhibitory effect of SIL, supporting a critical role of PP1 in NHE-1 dephosphorylation and inhibition.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation